ILUSTRASI DARI MPEG (MOVING PICTURE EXPERTS GROUP) DAN APLIKASINYA - Pamungkas Daud; Ganjar Turesna (EDUCARE, 2008)
MPEG is the important technology, which has gradual support in digital communication worlds especially in video and audio multimedia fields. This report is about performance of Moving Picture Expert Group (MPEG) system, completed with some example to illustrate how the system work and some implementation of MPEG system to make this System easy to understand and we can used the advantage for our purposed application that we need.Key Words: Digital,Communication,Multimedia